Debt To Equity Ratio Moderating Dividend Payout Ratio on Stock Price Volatility - Zulkifli, Zulkifli (IJBLE Scientific Publications Community Inc., 2024)
This research aims to analyze the influence of the dividend payout ratio on stock price volatility, moderated by the debt-to-equity ratio. The research adopts a quantitative approach, with the population consisting of companies listed in the LQ45 index on the Indonesia Stock Exchange. Sample selection is carried out using purposive sampling, with the criteria that companies must consistently be listed in the LQ45 index during the study period from 2019 to 2022. The data used in this study are secondary, and data analysis is conducted through the technique of panel data regression analysis. The empirical findings of this research indicate that the most appropriate model is the fixed effect. Based on the analysis results, the first hypothesis states that the dividend payout ratio does not have a significant direct effect on stock price volatility. Conversely, the second hypothesis states that the debt-to-equity ratio has a direct positive and significant effect on stock price volatility. Furthermore, the findings suggest that the third hypothesis states that the debt-to-equity ratio can strengthen the positive and significant impact of the dividend payout ratio on stock price volatility